2010
DOI: 10.1063/1.3499660
|View full text |Cite
|
Sign up to set email alerts
|

Two-parameter asymptotics in magnetic Weyl calculus

Abstract: This paper is concerned with small parameter asymptotics of magnetic quantum systems. In addition to a semiclassical parameter ǫ, the case of small coupling λ to the magnetic vector potential naturally occurs in this context. Magnetic Weyl calculus is adapted to incorporate both parameters, at least one of which needs to be small. Of particular interest is the expansion of the Weyl product which can be used to expand the product of operators in a small parameter, a technique which is prominent to obtain pertur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…In [17] it was shown that for Hörmander-class symbols, this product has an asymptotic development in ε and λ,…”
Section: Ordinary Magnetic Weyl Calculusmentioning
confidence: 99%
See 4 more Smart Citations
“…In [17] it was shown that for Hörmander-class symbols, this product has an asymptotic development in ε and λ,…”
Section: Ordinary Magnetic Weyl Calculusmentioning
confidence: 99%
“…The aim of this review is to show how recent advances in the theory of magnetic pseudodifferential operators (magnetic ΨDOs) (see [14,17] as well as section 2.2) can be used to extend the range of validity of the results of Panati, Spohn and Teufel derived via space-adiabatic perturbation theory (SAPT) [24] to magnetic fields with components in C…”
Section: Assumption 12 (Electromagnetic Fields)mentioning
confidence: 99%
See 3 more Smart Citations